PENGARUH KUAT TEKAN BETON DENGAN MENGGUANKAN BAHAN LIMBAH CUP PLASTIK (21-25) - Kosim Kosim; Ibrahim Ibrahim; Tri Sartika; Moudy Yustika Savira (PILAR, 2021)
ABSTRACTConcrete is a building material that consists of aggregates, water, and cement. The advantage of concrete as building structure material is have a high compressive strength, while the weaknes is low tensile strength. Along with the increasing uses of concrete in development, more efforts have been made to improve the quality of concrete or reduces the weakness. Many innovations have been made, such as by adding fiber and one of them from plastic cup waste. In this research, concrete with quality plan fc’22,5 was added with a count of Polyetylene Terephthalate (PET) type plastic cup waste with a percentage on mixture are 0 %, 0,1 %, 0,3 %, 0,5 %, 0,7 % and 0,9 % to the volume of fine aggregate with 3 samples of concrete cylinder by varying the age of care which is 3 days, 14 days, and 28 days. This mixture of plastic cup will become fiber concrete which will increase the compressive strength of the concrete. The results of the average compressive strength of the concrete were at the percentage of 0% is 24,02 MPa, at the percentage of 0,1 % is 19,55 MPa, at the percentage of 0,3 % is 23,53 MPa, at the percentage of 0,5 % is 24,20 Mpa, at the percentage of 0,7 % is 20,23 Mpa, and at the percentage of 0,9 % is 14,54 Mpa. The results of the compressive strength test of the concrete that using the plastic cup waste material increased by 0,16 % from normal concrete at percentage of 0,5 %.